Emerging erythromycin and clindamycin resistance in group A streptococci: Efficacy of linezolid and tedizolid in experimental necrotizing infection. (September 2020) - Bryant, Amy E.; Bayer, Clifford R.; Aldape, Michael J.; McIndoo, Eric; Stevens, Dennis L.
Highlights: Emerging antibiotic resistance in group A streptococci (GAS; S. pyogenes ) poses a major therapeutic dilemma. Oxazolidinones may be useful for severe macrolide/lincosamide-resistant GAS infections. Tedizolid and linezolid were studied in mice with cMLSB GAS myonecrosis. Both agents significantly delayed disease progression and improved outcomes. Data support oxazolidinone use in severe drug-resistant GAS human infections. Abstract: Objectives: Clindamycin (CLI) and erythromycin (ERY) resistance is increasing among group A streptococci (GAS) causing invasive disease and alternative treatments are urgently required. In this study, the efficacy of the newer oxazolidinone tedizolid (TZD) was compared with the first drug in this class, linezolid (LNZ), in experimental murine myonecrosis caused by ERY-susceptible/CLI-susceptible (ERY S /CLI S ) or ERY- resistant/CLI-resistant (ERY R /CLI R ) GAS. Methods: Normal adult outbred Swiss Webster female mice (10 per group) were infected intramuscularly with ERY S /CLI S (ATCC 12384) or ERY R /CLI R (15-003) GAS. Treatments began 4 h post-infection and continued for 72 h. TZD and LNZ (10, 20 and 40 mg/kg) were given intraperitoneally every 12 h. Saline, penicillin (PEN), CLI and ERY were given every 6 h. Survival and infection severity signs and symptoms were followed for 12 days. Results: Both GAS strains were susceptible to LNZ, TZD and PEN; strain 15-003 was confirmed as constitutively resistant to ERY and CLI. Blood levels following a 40 mg/kg dose of LZD and TZD were 30.9 ± 4.0 μg/mL and 21.9 ± 5.3 μg/mL, respectively. Both TZD and LNZ were highly efficacious for the treatment of severe experimental myonecrosis caused by ERY S /CLI S and, importantly, ERY R /CLI R GAS. Conclusion: In the current era of emerging macrolide/lincosamide resistance among GAS, these data support the use of TZD and LNZ as first-line antibiotics for the treatment of life-threatening GAS infections in humans.